DesignS: World Design Cities Shanghai Manifesto 2024, with an Introduction by Yongqi Lou and John Thackara - Yongqi Lou; Don Norman; John Thackara; Yrjö Sotamaa; Rosanne Somerson; Lorenzo Imbesi; Ezio Manzini; Patrick Whitney; Dan Hill; Jin Ma (She Ji: The Journal of Design, Economics and Innovation)
The DesignS: World Design Cities Shanghai Manifesto 2024 redefines the role of design in addressing contemporary polycrises—from climate collapse to AI-driven societal shifts—by advocating for a human-nature engagement paradigm. Building on predecessors like the 2008 Kyoto Design Declaration and 2014 DesignX Manifesto, this document positions design as a catalyst for regenerative economies, equitable innovation, and systemic resilience. Launched at the 2024 World Design Cities Conference in Shanghai, it emphasizes collaborative, cross-disciplinary, and cross-cultural dialogues to reshape the role of design and designers, design education, urban ecosystems, and AI integration, while prioritizing cities and their bioregions as living laboratories for sustainable futures.